Spousal Abuse in Nicholas Spark’s Safe Haven - Laura M. Sudargo; Theophilus J. Riyanto (Institute of Research and Community Outreach - Petra Christian University, 2014)
Kevin Tierney is the male main character in Safe Haven who does spousal abuse toward his wife, Erin. The analysis is on what spousal abusive behavior is and what the effects of the spousal abuse are in Nicholas Spark’s Safe Haven. The concept of spousal abuse proposed by Tina de Benedictis, Ph. D. is applied to reveal the spousal abuse done by Kevin and its effects on his spouse, Erin. In this research, I discover that Kevin does spousal abuse toward Erin that categorized into seven which are physical abuse, sexual abuse, destruction of property, verbal abuse, economic abuse, social isolation, and psychological abuse. Furthermore, Kevin’s abusive behaviors cause several effects on Erin that are categorized into four which are physical effects, psychological effects, social effects, and economic effects.